Finding greener grass on the other side of hill: Examining donor perceived brand equity in a moderating role of brand credibility. Issue 4 (30th October 2018) - Kashif, Muhammad; Fernando, P.M.P.; Samad, Sarminah; Thurasamy, Ramayah
Abstract : Purpose: The research concerning brand credibility of charity brands is scantly examined. The purpose of this paper is to examine the moderating role of brand credibility within the customer-based brand equity model to investigate donor perceived brand equity of charity brands. Design/methodology/approach: In a cross-sectional research design, a survey-based research strategy is followed to collect data from 448 active Muslim donors in Pakistan. The collected data are analysed by employing confirmatory factor analysis based on Smart PLS 2.0. Findings: The results indicate that donor perceived brand association, brand awareness and brand loyalty strongly relate to perceived brand equity of charity brands. The brand credibility moderates the relationship between perceived quality, equity and brand loyalty, and equity paths. Practical implications: The charity brands need to focus on building a strong brand image and reputation to uplift brand credibility which can be achieved by offering training programmes addressing various social causes such as HIV and Cancer prevention. Originality/value: The proposed moderating effects of brand credibility and its application to charity brands operating in an Asian Muslim country context are unique products of this study.